2011
DOI: 10.1007/s11368-011-0336-5
|View full text |Cite
|
Sign up to set email alerts
|

Zinc fractions and availability to soybeans in representative soils of Northeast China

Abstract: Purpose Limited information exists about the zinc (Zn) status of major soils in northeast China, and their ability to supply Zn to soybeans. This study aims to establish the critical concentrations of Zn in soil for plant growth, to characterize the Zn forms in soil, to correlate the concentration of various Zn forms with Zn uptake by soybeans, and to identify the most effective means of Zn application. Materials and methods Thirty-three soil samples were collected from farmland in 11 districts/sites (covering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 24 publications
3
13
0
3
Order By: Relevance
“…According to these results, EXCH-Zn and ORG-Zn pools can be considered labile pools that play significant roles in supplying Zn for plants. In agreement with our results, significant correlations between EXCH-Zn and ORG-Zn with Zn uptake by Soybean (Glycine max L.), (Han et al 2011) and Zn concentration in maize (Consolini 2003) concentration in all tissues of Corn (Zea mays L.) except the stem and grain. They also found significant correlation between ORG-Zn and Zn concentration in the stem, bran and grain of corn.…”
Section: Discussionsupporting
confidence: 92%
“…According to these results, EXCH-Zn and ORG-Zn pools can be considered labile pools that play significant roles in supplying Zn for plants. In agreement with our results, significant correlations between EXCH-Zn and ORG-Zn with Zn uptake by Soybean (Glycine max L.), (Han et al 2011) and Zn concentration in maize (Consolini 2003) concentration in all tissues of Corn (Zea mays L.) except the stem and grain. They also found significant correlation between ORG-Zn and Zn concentration in the stem, bran and grain of corn.…”
Section: Discussionsupporting
confidence: 92%
“…Han et al (2011) indicated that soybean growth was generally Science Publications AJABS positively correlated with Zn concentrations. Application of Zn also improved wheat growth (Nadim et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Optimum soybean yield can be obtained when Zn and P concentrations in the soil are greater than extension recommendations (Anthony et al, 2012a). Han et al (2011) added that soybean growth was mostly positively correlated with Zn fertilizer. Soybean yield increased with Zn fertilization, even in soils at above critical levels, so recommendations for Zn need to be revised (Inocencio et al, 2012).…”
Section: Ajabsmentioning
confidence: 99%
See 1 more Smart Citation
“…Há baixas perdas do nutriente por lixiviação, em razão de sua alta afinidade pelos coloides minerais do solo. Esse fato confere efeito residual prolongado às adubações com o micronutriente (Valladares et al, 2009;Han et al, 2011). Para Fageria (2000), o nível crítico de Zn em solos muito argilosos é de 0,8 mg dm -3 e, para Galrão (2004), de 1 mg dm -3 , com emprego do extrator Mehlich-1.…”
Section: Soybean Response To Zinc Fertilization In Soil With Contentsunclassified